The Core Can Be Accessed with a Bounded Number of Blocks - László Kóczy (Hungarian Academy of Sciences, Institute of Economics, 2005)
We show the existence of an upper bound for the number of blocks required to get from one imputation to another provided that accessibility holds. The bound depends only on the number of players in the TU game considered. For the class of games with non-empty cores this means that the core can be reached via a bounded sequence of blocks.
Keywords: C71; C73; C61; 330; core; indirect dominance